2014
DOI: 10.1177/0164027514537081
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Daytime Sleep in Nursing Home Residents

Abstract: A retrospective, cross-sectional study was conducted to describe the occurrence of daytime sleep (DS) and to examine factors associated with DS in nursing home residents. We used the Minimum Data Set 2.0 records of 300 residents in a nursing home from January 2005 to March 2010. Descriptive statistics, independent t-test, chi-square, Pearson correlations, and logistic regression were utilized in analysis. About 71.3% of the residents slept more than 2 hours during the day, and this was significantly associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 37 publications
1
21
1
5
Order By: Relevance
“…Even in studies that examined daytime sleep and cognition in older adults, napping was not assessed as a primary variable . Most studies categorized the study sample into two groups, such as nappers versus non‐nappers or napping less than 2 hours versus longer than 2 hours . There was thus a need for studies to examine the association between cognition and naps of different duration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even in studies that examined daytime sleep and cognition in older adults, napping was not assessed as a primary variable . Most studies categorized the study sample into two groups, such as nappers versus non‐nappers or napping less than 2 hours versus longer than 2 hours . There was thus a need for studies to examine the association between cognition and naps of different duration.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an epidemiological study in older women showed that objectively measured (actigraphy) napping for longer than 2 hours, as determined using actigraphy, was associated with greater risk of cognitive impairment . Prior studies also found that extended napping was associated with worse cognition . A longitudinal study found that napping for less than 1 hour and longer than 1 hour were negatively associated with incidence of cognitive impairment at 2‐year follow up after adjusting for multiple confounders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep disturbances are even more common in LTC residents and are often attributed to a high burden of comorbidities, lifestyle, and environmental factors (Lorenz, Harris, & Richards, 2011). For example, older adults living in LTC settings often have decreased physical activity, limited social interaction, minimal daylight exposure, and poor sleep hygiene (Li, Chang, & Porock, 2015). …”
Section: Introductionmentioning
confidence: 99%